COVID-19 crisis: a time for practical assessment of hygienic principles observance - S, Golmohammadi; M, Ahmadi; M, Faraji; M, Rahmanizadeh; B, Zarei; F, Chardoli; N, Ardalan; M, Rostamian; M, Ghasemi; Lorestani R, Chegene; A,T, Elahi; AH, Ondro (Penerbit Universiti Kebangsaan Malaysia, 2023)
Simultaneously with COVID-19 pandemic, numerous protocols have been developed to prevent the infection. COVID-19 can be more fatal in the bone marrow transplant ward because patients admitted to these wards have a weakened immune system. Assessment of the protocol specified for this wards and practical evaluation of the hygienic principles observance by the medical staff during COVID-19 pandemic can be a step towards saving the lives of the patients. Coinciding with COVID-19 pandemic, 40 patients underwent bone marrow transplantation at Imam Reza Hospital of Kermanshah, Iran from February 2020 to June 2022. A follow-up program was performed to evaluate the possibility of COVID-19 transmission and the rate of hygiene practice by medical staff. The principles of hygienic protocols were scored as a questionnaire in which the observance/non-observance method were applied. Real time-polymerase chain reaction (RT-PCR) based on three genes of the virus was used to diagnose the COVID-19 patients. The results of RT-PCR tests were negative in all patients who were hospitalised during the study. The rate of observance of the hygienic principles by the staff in the studied ward was 100%.The obtained result in the present study was a reflection of the step-by-step implementation of the hygienic protocol specified for bone marrow transplantation ward by the staff. The protocol specified for the bone marrow transplantation ward was highly overlapped with COVID-19 general hygienic guidelines.